Cytonuclear interactions remain stable during allopolyploid evolution despite repeated whole‐genome duplications in Brassica. (25th February 2019) - Ferreira de Carvalho, Julie; Lucas, Jérémy; Deniot, Gwenaëlle; Falentin, Cyril; Filangi, Olivier; Gilet, Marie; Legeai, Fabrice; Lode, Maryse; Morice, Jérôme; Trotoux, Gwenn; Aury, Jean‐Marc; Barbe, Valérie; et al.
Summary: Several plastid macromolecular protein complexes are encoded by both nuclear and plastid genes. Therefore, cytonuclear interactions are held in place to prevent genomic conflicts that may lead to incompatibilities. Allopolyploidy resulting from hybridization and genome doubling of two divergent species can disrupt these fine‐tuned interactions, as newly formed allopolyploid species confront biparental nuclear chromosomes with a uniparentally inherited plastid genome. To avoid any deleterious effects of unequal genome inheritance, preferential transcription of the plastid donor over the other donor has been hypothesized to occur in allopolyploids. We used Brassica as a model to study the effects of paleopolyploidy in diploid parental species, as well as the effects of recent and ancient allopolyploidy in Brassica napus, on genes implicated in plastid protein complexes. We first identified redundant nuclear copies involved in those complexes. Compared with cytosolic protein complexes and with genome‐wide retention rates, genes involved in plastid protein complexes show a higher retention of genes in duplicated and triplicated copies. Those redundant copies are functional and are undergoing strong purifying selection. We then compared transcription patterns and sequences of those redundant gene copies between resynthesized allopolyploids and their diploid parents. The neopolyploids showed no biased subgenome expression or maternal homogenization via gene conversion, despite the presence of some non‐synonymous substitutions between plastid genomes of parental progenitors. Instead, subgenome dominance was observed regardless of the maternal progenitor. Our results provide new insights on the evolution of plastid protein complexes that could be tested and generalized in other allopolyploid species. Significance Statement: Allopolyploid species exhibit biparental nuclear chromosomes but only uniparental plastid genomes. Such processes can deeply affect the functionality of protein complexes that are encoded by both nuclear and plastid genes. Our results demonstrate that repeated whole‐genome duplication events affect the retention of duplicated genes without altering cytonuclear interactions in the allopolyploid B. napus species.